SUPRACRUSTAL SEQUENCES OF THE BELOMORIAN MOBILE BELT: PROTOLITHS, AGE, AND ORIGIN - Myskova T.A.; Glebovitskii V.A.; Miller Yu.V.; L'vov A.B.; Kotov A.B.; Kovach V.P.; Zagornaya N.Yu. (My University, 2003)
Two section types are established in the Chupa nappe of the Early Precambrian Belomorian mobile belt (BMB) of the Baltic shield: one in the Lake Verkhnee Pulongskoe area of the stratotype region (Chupa Complex) and the other one in the tectonic window of the Kovdozero nappe (Kalikorva Complex). Both complexes are composed of supracrustal rocks represented by equal proportions of metavolcanics and metasediments (amphibolites and gneisses). Metavolcanics constitute 5-10% of the Chupa Complex and more than 50% of the Kalikorva Complex. Tholeiitic basalts prevailing among metavolcanics are accompanied by dacites and dacitic andesites. Poorly sorted graywackes with a low chemical index of (CIA = 51-55) are protoliths of metasediments. The dating results obtained for detrital and metamorphic zircons from dacites and graywackes (Bibikova et al., 2001), and the Sm-Nd isotopic-geochemical study of rocks imply coeval ages of the complexes and synchronism of volcanism and sedimentation. The supracrustal rocks were formed 2870 ± 30 Ma ago according to isotopic dates established for acidic volcanics (Bibikova et al., 2001). The detrital material of graywacke sequences could be derived from both the constituent volcanics of the complexes and the proto-ophiolites of mafic zones. An insignificant admixture of older clastic material derived from a remote provenance (presumably from the Karelian craton) cannot be ruled out as well. Local differences in volcanism and sedimentation were probably responsible for compositional difference between the Kalikorva and Chupa complexes and their constituting paragneisses. A low maturity and substantial proportion of mafic material were characteristic of protoliths for metasediments. The supracrustal rocks likely formed in the immature island-arc setting.
Keywords: Precambrian; Докембрий